1997
DOI: 10.1007/bf02457449
|View full text |Cite
|
Sign up to set email alerts
|

Research collaboration at Nordic universities

Abstract: Scientific collaboration has become a major issue in science policy. The need to survey and follow up such collaboration calls for statistical indicators sensitive enough to reveal the structure and change of collaborative networks. Bibliometric analysis of co-authored scientific articles is one promising approach. This study presents data generated from a comprehensive analysis of some 20,000 articles produced by 22 Nordic universities (Denmark, Finland, Iceland, Norway, Sweden) in 1993. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 5 publications
3
39
0
3
Order By: Relevance
“…The most common mean is through publication. 4 Garfield in 1970 also observed that a recent research focus can be reflected on its publication output. 5 Hence, a dramatic increase of SARS-related publications would be expected shortly after the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The most common mean is through publication. 4 Garfield in 1970 also observed that a recent research focus can be reflected on its publication output. 5 Hence, a dramatic increase of SARS-related publications would be expected shortly after the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in bibliometrics tend to use journal coauthorship to study networks. Some examples includeNewman (2001a,b) who study scienti…c collaboration in physics, biomedical research and computer science,Persson et al (1997) andMelin and Persson (1998) look at collaborative patterns of researchers at Nordic and European universities respectively andOkubo and Sjöberg (2000) examine internationalization tendencies of coauthorship in researching Swedish …rms. 9 This example is taken fromGranovetter (1973).…”
mentioning
confidence: 99%
“…This is an important topic in bibliometric research, as several studies confirm that multiple authorship tends to increase the impact of the research (Franceschet and Constantini 2010, Persson et al 2004, The Royal Society 2011. A study using data from 1993 showed increasing collaboration in Nordic authorship in different fields, although the data varied greatly across fields (Persson et al 1997). A more recent study also indicates an increase in collaboration among Norwegian scholars during the past decade (Smeby and Trondal 2005).…”
Section: (Rq2): What Are the Collaboration Patterns Of Nordic Authorsmentioning
confidence: 99%